Paradigma Program Car Free Day Dalam Upaya Menjaga Kelestarian Lingkungan Hidup Di Kota Medan - Gulo, Ika Dearni Putri; Tobing, Artha Lumban; Rajagukguk, Jonson (Research and Community Service UNIVERSITAS KALBIS, 2025)
Car Free Day (CFD) is a program that aims to reduce air pollution and increase public awareness of the importance of preserving the environment. This research aims to analyze the paradigm of the people of Medan City towards the Car Free Day program in an effort to preserve the environment. This research uses a qualitative method with a descriptive approach, where data is collected through observation and interviews with people who participate in Car Free Day. The research results show that the majority of people have a positive understanding of the Car Free Day program as a strategic step in reducing air pollution and supporting a healthy lifestyle. However, there are still challenges in implementing this program, such as a lack of active community participation, especially in protecting the environment, as well as a lack of outreach regarding the long-term benefits of Car Free Day. With this research, it is hoped that the government and other stakeholders can increase the effectiveness of the Car Free Day program through better communication strategies and the provision of more adequate facilities and infrastructure. Active community participation is also an important factor in the success of this program to preserve the environment in Medan City.